E-commerce Web-Based Application for Excellent Service Agency (ESA) Hospitality Training Center, Malang - Ratna Yulistiani; Andreas Nugroho Sihananto; Kartini; M. Arif Mardhavi; Edi Sugiyanto; Muhammad Afifudin (Nusantara Science and Technology Proceedings, 2022)
Excellent Service Agency (ESA) is a hospitality industry training center located in Malang City, East Java, Indonesia. This training center provides decent training for people who want to work in the hospitality industries such as hotels and restaurants. The one which makes a difference between ESA and its competitors is their commitment to providing training that is equivalent to other hospitality industry training institutions but at very affordable costs and they always channel students directly into the workplace market until their students land their first job. However, until now, ESA does not have an official website or e-commerce website to offer its services, so the ESA’s brand usually is only known by word of mouth. This ESA e-commerce website was developed with the CodeIgniter framework and MySQL Maria DB 5.0 database. The result is a company profile website that doubles as an e-commerce web ready to be used for ESA branding and marketing purposes.